The Interplay between Adipose Tissue Properties and Levels of NT-proBNP in People with HIV - Mads-Holger Bang Jacobsen; Anne Marie Reimer Jensen; Andreas Dehlbæk Knudsen; Thomas Benfield; Ruth Frikke-Schmidt; Børge Nordestgaard; Shoaib Afzal; Klaus Fuglsang Kofoed; Marco Gelpi; Susanne Dam Nielsen (Hindawi Limited, 2023)
Objective. We aimed to assess the association between low N-terminal pro-brain natriuretic peptide (NT-proBNP) and body mass index (BMI), adipose tissue distribution, adiponectin, and HIV-specific risk factors among people with HIV (PWH). Methods. We included 811 PWH with measurement of height, weight and waist circumference, blood samples analyzed for NT-proBNP, and visceral-(VAT) and subcutaneous (SAT) adipose tissue areas measured from CT-scans. Low concentrations of NT-proBNP were defined as concentrations below the limit of quantification (5.9 pmol/L). Associations were explored with multivariable logistic regression analyses adjusted for relevant confounders. Results. We identified 471 (58%) individuals with low concentrations of NT-proBNP. Increasing BMI was associated with higher odds of low NT-proBNP (adjusted OR (aOR) 1.06 (95% CI: 1.01-1.11) per 1 kg/m2). Central obesity and large areas of VAT were associated with higher odds of low NT-proBNP (aOR 1.66 (1.16-2.36) and aOR 1.69 (1.09-2.62), respectively). Higher adiponectin was associated with lower odds of low NT-proBNP (aOR 0.86 (0.79-0.95) per 10% increase). No associations were found between low NT-proBNP and HIV-specific risk factors. Conclusions. In PWH, low NT-proBNP is associated with an adverse adipose tissue profile with high BMI, central obesity, accumulation of VAT, and low adiponectin.